Internal audit and governance of Moroccan local authorities: Drafting a conceptual model - SIMOU, Zineb; DAOUI, Driss (Edelweiss Applied Science and Technology, 2025)
This article proposes a conceptual model analyzing the contribution of internal audit to the governance of Moroccan local authorities. Based on a qualitative comparative analysis of 22 empirical studies, the model explores how internal auditing strengthens transparency, accountability, and efficiency in local governance. It identifies mediating factors such as organizational climate and process optimization, as well as moderating factors, including leadership and citizen engagement. The framework emphasizes the strategic role of internal audit as the third line of defense, highlighting its independence, competence, communication, and follow-up mechanisms. Findings from recent Moroccan and international studies show that internal audit enhances resource management and policy implementation but faces challenges related to limited autonomy, weak enforcement of recommendations, and lack of professionalization. This article provides a theoretical foundation for future empirical research through interviews and surveys with local officials and managers. By integrating diverse perspectives, the model contributes to a better understanding of governance dynamics in developing countries and offers practical insights to improve transparency and citizen participation within Moroccan local governments.